Utility of SCORE2 risk algorithm for predicting life course accelerated frailty and physical function decline. Issue 1 (26th December 2022) - Li, Chenglong; Ma, Yanjun; Hua, Rong; Zheng, Fanfan; Xie, Wuxiang
Abstract: Background: Frailty is a dynamic process that increases with ageing, while it remains unclear whether cardiovascular disease (CVD) risk algorithm could predict life course dynamic frailty trajectories, for example, the longitudinal patterns of how frailty evolves with time. We intended to examine the predictive utility of the Systemic Coronary Risk Estimation 2 (SCORE2) algorithm for life course accelerated frailty and physical function decline, in comparison with the precedent SCORE algorithm. Methods: Longitudinal data regarding accumulation of deficits frailty index (FI) and physical function (grip strength, gait speed, peak expiratory flow and timed chair rises) were drawn from the English Longitudinal Study of Ageing (ELSA) and Health and Retirement Study (HRS), two nationally representative cohorts with community‐dwelling adults aged ≥50 years. SCORE and SCORE2 were calculated at baselines following European Society of Cardiology guidelines. A group‐based trajectory modelling approach was used for identifying potential life course frailty trajectories, based on 14‐ and 12‐year FI data in the ELSA and HRS. Modified Poisson regression and linear mixed model were applied for analysing associations between SCORE2 with accelerated frailty trajectory and physical function decline, respectively. Receiver operating characteristic curve (ROC) analysis was conducted to evaluate predictive utility for accelerated frailty increase trajectory of SCORE and SCORE2, with the area under the curve (AUC) compared using the paired DeLong's test. Results: A total of 4834 participants from the ELSA and 7815 participants from the HRS were included (mean age: 64.0 ± 9.2 and 65.4 ± 9.9 years; men: 44.3% and 41.4%, respectively). Three frailty trajectories were consistently identified in both cohorts: (1) stable frailty increase ( n = 3026 in ELSA and 4004 in HRS); (2) moderate frailty increase ( n = 1325 in ELSA and 2955 in HRS); (3) accelerated frailty increase ( n = 483 in ELSA and 856 in HRS). Each 10% increment in SCORE2 risk was associated with the higher risk of accelerated frailty increase (risk ratio [RR]: 3.58, 95% confidence interval [CI] [3.22, 3.98], P < 0.001 in ELSA; RR: 1.61, 95% CI [1.56, 1.67], P < 0.001 in HRS) and faster declines in all physical function measurements. SCORE2 algorithm showed good accuracy for predicting accelerated frailty increase (area under the curve [AUC] in ELSA: 0.759; HRS: 0.744), with better performance than the SCORE (AUC in ELSA: 0.729; HRS: 0.700) in both cohorts ( P < 0.001 for comparison). Conclusions: SCORE2 algorithm could serve good utility for predicting life course accelerated frailty increase and physical function decline among community‐dwelling non‐frail adults aged ≥50 years.